Sparganosis –a rare case report - Agrawal, Manish; Agrawal, Ekta; Murthy, R (International Journal of Medical Research and Review, 2015)
Sparganosis is a parasitic infection caused by the plercercoid larvae of diphyllobothroid tapeworms belonging to the genus Spirometra. It is a rare disease of human as man is not a natural host of spirometra species. Diagnosis of latter is difficult as it mimics other conditions that commonly cause subcutaneous or visceral fluid collection. Here we report a case of Sparganosis in a man who presented with a swelling over left cheek. It was confirmed by pathological and microbiological examination. To the best of our knowledge, this is the first case from Central India where sparganum was isolated from a swelling.